(untitled) (Swiss Medical Weekly, 2021)
Assisted reproductive technology (ART) is an efficacious and frequently used treatment of infertility. Multiple births resulting from the widespread practice of transfer of more than one embryo per treatment trial have reached epidemic proportions. Since the revision of the Swiss law on ART in September 2017, up to 12 embryos per couple may now be developed in vitro and cryopreserved in Switzerland. This potentially allows for the selection and transfer of only one embryo to avoid multiple birth with ART. We decided to offer transfer of one embryo to all infertile patients undergoing ART in our institution. In this retrospective cohort study the cumulative pregnancy and live-birth rates after universal transfer of one embryo from January 2018 to December 2019 were analysed. The cumulative pregnancy rate per oocyte collection and up to five transfer cycles was as high as 48.9%, whereas the cumulative live-birth rate reached 33.4% and none were multiple births. These results were age-dependent, with best outcome in patients aged 37 years or younger. When still remaining cryopreserved embryos were taken into account, the cumulative birth-rates could exceed 60% per oocyte collection in all age groups. The consequent adoption of a single embryo transfer significantly reduced the incidence of multiple births in the department of obstetrics and the number of prematurely born infants resulting from multiple pregnancies in the department of neonatology. Universal elective single embryo transfer is feasible in Switzerland, benefits infertile couples treated with ART and reduces the number of multiple births in obstetrics and of newborn children hospitalised into neonatal care.